Optimization of Sol-Gel-Derived TiO2-Based Thin Films for Methylene Blue Photodegradation: A Systematic Review - Kormil Saputra; Suci Indriati Putri; Dian Wijaya Kurniawidi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
TiO₂-based thin films are among the most widely developed photocatalytic materials for degrading organic pollutants because of their chemical stability, low toxicity, relatively low production cost, and compatibility with various deposition methods. However, their photocatalytic performance is strongly influenced by synthesis parameters, crystal phase, particle size, crystallite size, morphology, substrate type, and material modification strategies. This review aims to analyze the relationship between TiO₂ thin-film synthesis parameters and methylene blue degradation efficiency based on 14 articles published between 2015 and 2024. The findings indicate that the sol-gel method is the most dominant synthesis approach, applied through dip coating, spin coating, drop coating, spray coating, and combinations with electrodeposition and magnetron sputtering. A thermal treatment range of 450–600 °C was identified as the most effective condition because it promotes anatase crystallinity while minimizing excessive crystal growth and agglomeration. High photocatalytic performance was generally associated with anatase phase dominance, small to moderate crystallite size, open or uniformly distributed morphology, and material modifications that improve charge separation. Among the reviewed modified materials, the optimum condition was achieved in 40PVP/SnO₂/TiO₂ thin films calcined at 600 °C for 2 h, with a crystallite size of approximately 8.6 nm and methylene blue degradation of about 90.4%. For pure TiO₂ thin films, the optimum condition was obtained through heat-assisted sol-gel spin coating with 48 h sol aging and annealing at 600 °C, producing a crystallite size of approximately 10–15 nm and methylene blue degradation of about 92.90%. This review concludes that optimizing TiO₂ thin films should not focus solely on reducing crystallite size but should integrate control of phase composition, crystallinity, morphology, and charge separation efficiency. The study contributes to photocatalytic material development by synthesizing key synthesis-performance relationships that can guide future optimization of TiO₂-based thin films for organic pollutant degradation.